The Relationship Between Diverse Food Consumption and Stunting in Infants Aged 6-24 Months in Indonesia - Ardhanareswari Dhiyas Anindya; Trini Sudiarti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Inadequate feeding practices result in malnutrition and stunting which results in delayed growth and development of infants and children. The aim of the study was to determine the relationship between the consumption of various foods and the incidence of stunting in infants aged 6-24 months in Indonesia. The method used in writing this article is the literature review, which is a literature search both nationally and internationally carried out using a database. Article searches are conducted using four electronic databases, namely Google Scholar, Researchgate, PubMed Central, and ScienceDirect. The search returned 11 articles after removing duplicate articles, 8 remaining. After screening the titles and abstracts which are not in accordance with the themes included, are letters/reports/brief communications/chapters. The final screening resulted in 8 articles that met the inclusive criteria. The results of the study show that food diversity in Breast Milk Mp is one of the indicators used to assess nutritional adequacy in preventing stunting. It can also be used to see an overview of the food groups consumed by children aged 6-23 months in assisting breastfeeding. It is recommended for cadres and health workers to be more active in providing counseling about complementary foods for the development of toddler nutrition and it is suggested to provide nutrition training to mothers who have toddlers in order to increase mothers' knowledge about nutritious food for toddlers. Keyword: Babies 6-24 months, Breast Milk, Food, Stunting, Various